If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 55 = 3x + 244 Reorder the terms: 55 + 6x = 3x + 244 Reorder the terms: 55 + 6x = 244 + 3x Solving 55 + 6x = 244 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 55 + 6x + -3x = 244 + 3x + -3x Combine like terms: 6x + -3x = 3x 55 + 3x = 244 + 3x + -3x Combine like terms: 3x + -3x = 0 55 + 3x = 244 + 0 55 + 3x = 244 Add '-55' to each side of the equation. 55 + -55 + 3x = 244 + -55 Combine like terms: 55 + -55 = 0 0 + 3x = 244 + -55 3x = 244 + -55 Combine like terms: 244 + -55 = 189 3x = 189 Divide each side by '3'. x = 63 Simplifying x = 63
| m^3=8/125 | | j-3/2=2 | | -8+3.5=1-4(3.5) | | -3n+18=-6(n+1) | | 12x-34=46+7x | | 12b=.2 | | (6g-9)+1/3(15-9g)= | | 12+3d=d | | 5.7+b=23 | | -4x+82=-86-10x | | 25=n-(3) | | R^2=-96 | | (0.01)(1)+0x=0.02(x+1) | | 24x^2-58x+40=7 | | 2/3y-12 | | 17=-d | | -2=j-3/2 | | 3.2+9.3x=0.2x+1.4 | | -5+6f=5f+2 | | 3/2(5x-4)+1=1/3x-2(x-5) | | -8(x+2)=-3x-31 | | -1/2-7=_ | | 2/8k=16/24 | | 6y-10+6y+10= | | -6g+8=-4g | | 5x-8=6x+15 | | -5t^2-8t=-120 | | -3b+4b=14-b | | 10x+-5=3x+9 | | 13=-3n+11-n | | 1/12x=3 | | 7(5x+3)=371 |